The Ominous Decade in light of the Bicentennial: New Perspectives on the Second Absolutist Restoration in Spain (1823-1833) - París, Álvaro (Hispania Nova, 2022)
The Second Absolutist Restoration (1823-1833) remains one of the least known periods of Spanish Modern History. On the bicentenary of the restoration of 1823, this paper aims to offer an overview of the period that points out both the historiographical advances as well as the blind spots and the paths to be followed. The reinterpretation of the absolutist decade requires resolving the apparent contradiction between the administrative reforms (which built the foundations of the Liberal State) and the repressive nature of the regime. Through two sections –the first dedicated to the king and the second to politics– this paper tries to analyse the logic of Ferdinand VII’s system of government and the emergence of two opposing factions that mobilized their supporters to implement two incompatible models of restoration: the moderate absolutists and the ultra-royalists.